Usual gait speed is inversely associated with depression in middle-aged and older adults: A cross-sectional study in Korea - Jae Ho Park; Joong-Yeon Lim; Hyun-Young Park (PLoS ONE, 2026)
Background Depression is a serious mental disorder and leading cause of suicide. This study investigated the association between usual gait speed (UGS) and risk of depression. Methods Data from 2,419 participants from a community-based Korean cohort were analyzed. Participants were categorized into sex-specific UGS tertiles (low, mid, or high). Depression was defined based on a previous physician diagnosis, current use of antidepressants, or a score of ≥6 on the Korean version of the Geriatric Depression Scale-Short Form (SGDS-K). Multiple linear and logistic regression models were used to assess the association between UGS and SGDS-K scores and estimate the odds ratios (ORs) with 95% confidence intervals (CIs) for the risk of depression, respectively. Results Prevalence rates of depression were 13.33% and 26.29% among men and women, respectively. Compared with participants with low UGS, men with high UGS had a 50% (OR=0.50; 95% CI [0.29, 0.86]; p < 0.05) lower risk of depression, and women with mid and high UGS had a 43% (OR=0.57; 95% CI [0.41, 0.79]; p < 0.001) and 44% (OR=0.56; 95% CI [0.38, 0.82]; p < 0.01) lower risk, respectively. The SGDS-K scores were lowered by 0.14 (95% CI [–0.23, –0.04]; p < 0.01) and 0.33 points (95% CI [–0.45, –0.21]; p < 0.0001) in men and women, respectively, with each 0.1 m/s increase in UGS. Conclusions Hence, faster UGS was significantly associated with a reduced risk of depression in both sexes. Thus, maintaining a fast UGS may have protective benefits against the risk of depression.